2001
DOI: 10.1037/0278-7393.27.1.157
|View full text |Cite
|
Sign up to set email alerts
|

Telling stories: The perils and promise of using verbal reports to study math strategies.

Abstract: The problem size effect in adult arithmetic performance is generally attributed to direct retrieval processes operating on a network representation in long-term memory. J. LeFevre and her colleagues (J. LeFevre, J. Bisanz, et al., 1996; J. LeFevre, G. S. Sadesky, & J. Bisanz, 1996) challenged this explanation using verbal report evidence that adults also use time consuming nonretrieval strategies to solve simple addition and multiplication. The authors replicated J. LeFevre and colleagues' methods, but added i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
2
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(170 citation statements)
references
References 40 publications
4
161
2
3
Order By: Relevance
“…The self-report methodology has nonetheless been criticised on the grounds that, when asked to describe mental processing, people may change or be unable to accurately describe their behaviours (Kirk & Ashcraft, 2001;Smith-Chant & LeFevre, 2003). Additionally, individual differences and instructional demands may bias verbal reports and the solution procedures that are reported (Kirk & Ashcraft, 2001;Smith-Chant & LeFevre, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The self-report methodology has nonetheless been criticised on the grounds that, when asked to describe mental processing, people may change or be unable to accurately describe their behaviours (Kirk & Ashcraft, 2001;Smith-Chant & LeFevre, 2003). Additionally, individual differences and instructional demands may bias verbal reports and the solution procedures that are reported (Kirk & Ashcraft, 2001;Smith-Chant & LeFevre, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To what extent multiplication problems are solved by retrieval in adults is a matter of considerable debate (e.g., Kirk & Ashcraft, 2001;. If multiplication problems are not solved primarily by retrieval but by such strategies as repeated addition or multiplication by 10 followed by subtraction [e.g., 9 ϫ 8 ϭ (10 ϫ 8)Ϫ8], it might be that some or even all of the major effects could be attributed to nonretrieval strategies.…”
Section: Retrieval and Nonretrievalmentioning
confidence: 99%
“…For this purpose, verbal reports of the strategy used by each participant were collected. However, because it has been observed that the method of verbal report alters the strategies that participants would have spontaneously used (Kirk & Ashcraft, 2001), verbal reports were collected in a separate session administered after the experimental sessions. Our main analyses focused on those participants who reported retrieving the answer of all the very small additions studied by Barrouillet and Thevenot (2013) and almost all the small additions (i.e., with a sum 6 10).…”
Section: The Present Studymentioning
confidence: 99%